Extensive literature search on organic arsenic in food. Issue 9 (14th September 2022) - Licht, Oliver; Breuer, Franziska; Baskirov, Alina; Blümlein, Katharina; Kellner, Rupert; Pallapies, Dirk; Partosch, Falko; Pieczyk, Bianca; Schwonbeck, Susanne; Wiedemeier, Petra; Zwintscher, Ariane
Abstract: An Extensive Literature Search (ELS) to collect and identify all studies published since 2009 and relevant to the topic organic arsenic in combination with the substance group characterisation, occurrence in food and toxicity was performed in the three databases PubMed, Web of Science and Scopus for eight scientific Areas. After combination of the searches from the three databases and removal of the duplicates, the total number of references was 6998. The evaluation of all retrieved references for relevance by screening the title and abstract and applying eligibility criteria (inclusion/exclusion) for group (a) small methylated arsenic species resulted in a total number of relevant references for 406 for Area 1a, 246 for Area 2a, 287 for Area 3a, 31 for Area 4a, 56 for Area 5a, 108 for Area 6a, 38 for Area 7a and 95 for Area 8a. In comparison a smaller number of relevant references was retrieved for substance group (b) arsenic species other than small methylated species and including any other organic species: 352 for Area 1b, 73 for Area 2b, 257 for Area 3b, 14 for Area 4b, 23 for Area 5b, 30 for Area 6b, 57 for Area 7b, and 18 for Area 8b. However, these were assigned to be relevant for more than one Area or substance group. All relevant references were additionally screened to extract available information at a high level by full paper review. In this step, some references were excluded due to the lack of relevant information. The total number of relevant references is further reduced to 1239.